Data Loggers for High-Temperature Industrial Environments - Roberto Cecchi; Alessandro Catania; Christian Sbrana; Massimo Macucci; Sebastiano Strangio; Giuseppe Iannaccone (IEEE Access)
Monitoring temperature in harsh environments is necessary for many applications in space exploration, oil and gas production, renewable energy, and process manufacturing. There are several high-temperature scenarios where placing data loggers close to sensors is mandatory. For instance, the fabrication of high-quality photovoltaic cells requires monitoring the thermal processes inside sealed ovens or along conveyor belts, with temperature often well beyond the operating range of industrial-grade electronic components. In this work, we propose two distinct data acquisition systems to address this challenge. The main novelty of the first data logger over existing solutions is that it leverages specialized high-temperature resistant components to withstand temperature up to 200°C, and, therefore, can be used inside industrial ovens without the need for thermal protection. The second system, instead, employs cheaper and more efficient industrial-grade components, but occupies a larger volume for thermal shielding. We discuss the design of both systems at the hardware and software level, with an emphasis on the key issues related to high-temperature operation. We characterize and test the two data loggers in real case scenarios, demonstrating their robustness where common platforms are inadequate. The two systems achieve a resolution of 0.48°C and 0.12°C, and an accuracy of +/−0.6°C and +/−0.4°C, respectively. Our findings can be generalized and translated to a wide range of industrial applications in harsh environments.